The Place of the Educational Discipline «Simulation Modeling in the Work of a Hotel and Restaurant Complex» in the Process of Training Specialists in Professional Education - Feshchuk, Yurii (Pedagogical Discourse, 2022)
The need for introducing the latest information technologies in the hospitality industry has been determined based on theoretical and empirical studies. The article proposes the content of the educational discipline «Simulation modeling in the work of a hotel-restaurant complex» in the process of training undergraduate students in the specialty 015.16 «Professional education (Services (Hotel and restaurant business))». It is asserted that the content of the proposed discipline should take into account modern trends in the development of education and the requirements for the training of a qualified student of higher education with the appropriate qualification (The Bachelor of Science degree in Vocational Education (Service Field), Hospitality Vocational Instructor and Specialist). The program of the academic discipline, the topics of lectures, and practical classes have been defined. The following topics are offered for courses: FlexSim: general information; library of FlexSim objects; logic building tools in FlexSim; control elements in FlexSim; the process of model simulation in FlexSim. Practical classes have been developed on the following topics: the study of the FlexSim system interface; selection of objects from the FlexSim library for the selected model of the hotel-restaurant complex; survey of tools for building logic in FlexSim; study of control elements in FlexSim; analysis of the simulation process of the hotel-restaurant complex model in FlexSim; study of logic construction tools in FlexSim; study of control elements in FlexSim; survey of the modeling process of the hotel-restaurant complex model in FlexSim. Acquired theoretical knowledge and practical skills from this discipline will be helpful to future professional education specialists during industrial practice; internship at hotel and restaurant business objects; execution of case studies; work on a document conferring a qualification (diploma); participation in academic mobility programs.